Pengembangan Panduan Bimbingan Karir Berbasis Pendidikan Kecakapan Hidup (Life Skill) dengan Pendekatan Teori Karir Super untuk Meningkatkan Perencanaan Karir Siswa di SMK Negeri 2 Singaraja - Jhon Riyanto; Luh Putu Sri Lestari; Kadek Suranata (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This is the development research which aims to develop a career guidance guide product based on life skills with a super career theory approach to improve student career planning. This study uses the 4D development research that consists of Define, Design, Develop, and Disseminate. This research involved 3 lecturers of the Undiksha FIP guidance counselling study program. Researcher tested the validity of the product being developed. Based on the results of expert's assessment, it was found that the product met the requirements and was suitable for use in career guidance services found that the product met the requirements. An effectiveness test was carried out to determine the developed career guidance guide was effective in improving student career planning. The hypothesis test stated that the Handbook was effective with an Effect Size in the high category. The result can be concluded that the developed career guidance guide is effective and belongs to the high ES category to increase students' career planning.